(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
The meat grinder serves as a fundamental circuit for inductive pulsed-power supply (IPPS). Several derivative circuits have been constructed and suggested based on a meat grinder, including inverse commutation with semiconductor devices (ICCOS), self-charged capacitor and thyristor (SECT), capacitor pulse forming unit (CPFU), and auto-charging commutating capacitor (ACC). This research presents a simulation-based parametric investigation in which capacitance and pre-charging voltage are modified from 100 μF to 800 μF and from 600 V to 1200 V, respectively, with a full analysis of load current characteristics observed. It was noted that load current rises with an increase in capacitance or pre-charging voltages; however, with ACC-based architecture, load current diminishes as capacitor size grows. The ICCOS-based topology exhibited elevated load peaks of 9.26 kA and 16.12 kA for the first and second peaks, respectively, at 800 μF and 1200 V.